The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.radonc.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of small bowel dose–volume and acute toxicity in conventionally-fractionated rectal cancer radiotherapy

Abstract: Highlights Acute GI toxicity is highly prevalent and dose-limiting in the treatment of rectal cancer  The dose-volume relationship for the small bowel is inadequately understood  We have conducted meta-analysis of published dose-volume-histogram datasets  We found a significant increase in toxicity with increased irradiated volume  We also showed increased risk with increased dose for a given irradiated volume Acknowledgements: MAH is funded by UK Medical Research Council grant MC_UU_00001/2 ResultsOn fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…Toxicity has been mostly reported in prostate patients that are treated with higher doses than rectal cancer. Holyoake et al [ 33 ] conducted a meta-analysis looking at the mean difference in volume for small bowel for different dose levels between grades 0–2 and grade 3 toxicity and a toxicity risk for V10Gy and V40Gy received by normal fractionated radiotherapy. In all included studies the patients were treated with chemotherapy concomitantly.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity has been mostly reported in prostate patients that are treated with higher doses than rectal cancer. Holyoake et al [ 33 ] conducted a meta-analysis looking at the mean difference in volume for small bowel for different dose levels between grades 0–2 and grade 3 toxicity and a toxicity risk for V10Gy and V40Gy received by normal fractionated radiotherapy. In all included studies the patients were treated with chemotherapy concomitantly.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chen et al showed that the small bowel volume that received 45 Gy was larger when IMRT was delivered on an empty bladder than when IMRT was delivered on a full bladder [ 12 ]. Furthermore, recent meta-analysis reported that grade 3 or more small bowel toxicity was related to multiple parameters in small dose area (range, 5–35 Gy) rather than traditional parameters related to 45 Gy [ 14 ]. Adequate bladder filling can reduce the small bowel volume affected by small dose area.…”
Section: Discussionmentioning
confidence: 99%
“…Radiochemotherapy is a widely accepted treatment mode in patients with locally advanced rectal cancer. It can result in a significant reduction in the local recurrence rate by up to 30% and improve the 5-year disease-free survival rate [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%